APLIKASI PENENTUAN LOKASI PEMBUKAAN USAHA AGRIBISNIS BERBASIS ASPEK LINGKUNGAN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Ineke Nursih Widyantari (AGRICOLA, 2014)
This study aims to create software that can help decision making to determine the ideal location for the opening agribusiness based on environmental aspects. The software is designed applications that are built using computer programming language based on the better alternative and apply the principles of system development by applying the method of decision-making selection of the best alternative to certain criteria, namely Simple Additive Weighting (SAW). Research carried out by determining the weighting of criteria to determine the value of the interest rate criterion of the weight value of the weight values and other criteria to assess each of the alternatives available to each of the existing criteria. Subsequent processing to be normalized to the result of the valuation criteria of the alternatives and the results are in total them to get the preference value of each alternative, the alternative with the greatest preference value is an alternative that has the best value for the chosen and accepted.Results of testing performed by the black box method and Acceptance testing performance category and have successfully passed the tests, so that the expected functionality of the system has been running well.